Auricular acupressure promotes uterine involution after cesarean section: A randomized controlled trial - Shu-xin Wang; Jing-chun Zeng; Ting Li; Wan-lan Zhang; Yan-fang Li; Run-jin Zhou; Zi-jun Liu; Yu-ling Liu; Xun Zhuang; Rui Zhang; Li-ming Lu; Guo-hua Lin (Integrative Medicine Research)
Background: Postpartum subinvolution of the uterus is a more common condition after cesarean section. Auricular acupressure (AA) is widely used for the treatment of postpartum diseases. However, few studies have explored the effects of AA as a treatment of uterine involution following cesarean section to date. This study aimed to assess the efficacy and safety of AA for uterine involution after cesarean section. Methods: A total of 109 women who underwent cesarean section participated in this study. They were randomly allocated to either real AA or sham AA in a 1:1 ratio by a computer program. For 3 days, the real AA and sham AA groups received treatment 3 times daily. A series of assessments at 42 days after cesarean section, namely on the uterine size, the incidence of hydrometra, the first anal exsufflation time, bleeding volume at 6 hours, bleeding volume at 6–24 hours along with other general assessments were carried out. Results: A total of 89 women completed the study. The uterine size at 42 days after a cesarean section was 6.3 cm smaller in the real AA group than in the sham AA group (P < 0.01). The incidence of hydrometra on day 42 postpartum was lower in the real AA group than in the sham AA group (P < 0.01). The lochia duration and the first anal exsufflation time after cesarean section were shorter in the real AA group than in the sham AA group (P < 0.05). Conclusion: AA improves uterine involution after cesarean section. Trial registration: ChiCTR1800015569.